1983
DOI: 10.1111/j.1467-8306.1983.tb01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Capital

Abstract: Using yearly estimates of US. interstate migration and state-level capital stocks we explore the relationships between migration and capital in a time-series framework for the period 1958-1975. The analysis shows that capital growth leads in-migration for fast-growing states, although no obvious relationship is apparent for some rapidly growing areas. However, for slow-growth states the relationships are more complex and interwoven. Box-Jenkins techniques and tests of causality are utilized to describe the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The manufacturing firm responds to new directions of capital flows (BLACKLEY, 1986;HICKS, 1987), for example, by relocation. Many argued that firms relocate so as to exploit a relatively immobile and vulnerable labour force (CLARK and GERTLER, 1983;PEET, 1983;WALKER, 1978). Others emphasized the transition from Fordist production systems to vertical disintegration which is more flexible and capable of freeing plants from traditional locations and factors oflocation (MASSEY, 1988;SCOTT, 1986SCOTT, , 1988STORPER and WALKER, 1989).…”
Section: Polarization a N D Polarization Reversalmentioning
confidence: 99%
“…The manufacturing firm responds to new directions of capital flows (BLACKLEY, 1986;HICKS, 1987), for example, by relocation. Many argued that firms relocate so as to exploit a relatively immobile and vulnerable labour force (CLARK and GERTLER, 1983;PEET, 1983;WALKER, 1978). Others emphasized the transition from Fordist production systems to vertical disintegration which is more flexible and capable of freeing plants from traditional locations and factors oflocation (MASSEY, 1988;SCOTT, 1986SCOTT, , 1988STORPER and WALKER, 1989).…”
Section: Polarization a N D Polarization Reversalmentioning
confidence: 99%
“…Although the application of time series analysis has been limited, by lack of regional time series data (Greenwood 1985), it has been applied to interregional migration by Clark (1981, 1982a andb), Clark and Ballard (19801, Clark and Gertler (1983), and Tabuchi (1985Tabuchi ( , 1988. Indeed Clark and Gertler (1983) have shown that the neoclassical model may not be validated when detailed time series analysis is used.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…New productive forces have been produced and distributed across the face of the earth' (1982, p. 373). But if 'uneven development' is integral to capitalism, ought it not to be central to the entire theory, and not just the last three chapters (Clark, 1983)? After all, Harvey himself (1984a, p. 8) has told us that: 'The insertion of spatial concepts into social theory has not yet been successfully accomplished.…”
Section: Continued The0 Y-buildingmentioning
confidence: 99%